1999
DOI: 10.1046/j.1440-169x.1999.00419.x
|View full text |Cite
|
Sign up to set email alerts
|

Significant role of laminin‐1 in branching morphogenesis of mouse salivary epithelium cultured in basement membrane matrix

Abstract: Mouse submandibular epithelium shows branching morphogenesis in mesenchyme-free conditions when covered with a basement membrane matrix (Matrigel) in medium supplemented with epidermal growth factor. In the present study, the role of laminin-1 (LN1), a major glycoprotein of Matrigel, in this culture system was defined. When the epithelium was cultured in a LN1-nidogen gel, the epithelium showed much branching, comparable to that observed with Matrigel. By electron microscopy, only a felt-like matrix was formed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
4

Year Published

1999
1999
2009
2009

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 45 publications
0
32
0
4
Order By: Relevance
“…We isolated the epithelial rudiments free from mesenchyme and cultured them in Matrigel with reduced growth factor. Under this culture condition, the epithelial rudiments were unable to grow and form branches (Hosokawa et al, 1999). Interestingly, addition of Sema3A into this culture did not stimulate branching of the SMG epithelia (Fig.…”
Section: Sema3a Restricts the Movement Of The Cultured Smg Epithelialmentioning
confidence: 83%
“…We isolated the epithelial rudiments free from mesenchyme and cultured them in Matrigel with reduced growth factor. Under this culture condition, the epithelial rudiments were unable to grow and form branches (Hosokawa et al, 1999). Interestingly, addition of Sema3A into this culture did not stimulate branching of the SMG epithelia (Fig.…”
Section: Sema3a Restricts the Movement Of The Cultured Smg Epithelialmentioning
confidence: 83%
“…Branching morphogenesis of SMGs in vitro involves EGF signaling (Kashimata and Gresik, 1997;Kashimata et al, 2000;Morita and Nogawa, 1999), integrin α6, laminin-1 (Hosokawa et al, 1999;Kadoya et al, 1995), the TNF/TNFR1/IL6 pathways (Melnick et al, 2001b;Melnick et al, 2001c), and FGF7 (Morita and Nogawa, 1999). Fibroblast growth factors (FGFs) and their receptors (FGFRs) are important in many developmental events, including branching morphogenesis in other organs (Martin, 1998;Metzger and Krasnow, 1999;Ornitz, 2000;Spencer-Dene et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The salivary epithelium thereby was proved to perform branching morphogenesis when embedded in a laminin-rich basementmembrane-like matrix and stimulated by epidermal growth factor (EGF; Nogawa and Takahashi, 1991). Since then, many studies have reported the involvement of EGF family ligands (transforming growth factor ␣, heparin-binding EGF, and neuregulin) and laminins in the branching morphogenesis of the salivary gland (Kadoya et al, 1995;Kashimata and Gresik, 1997;Hosokawa et al, 1999;Kashimata et al, 2000;Umeda et al, 2001;Koyama et al, 2003;Miyazaki et al, 2004;Kadoya and Yamashina, 2005). During the development of the mesenchyme-free culture of salivary epithelium, we introduced a serum-supplemented medium but paid little attention to the serum, because we had typically added serum as a source of nutrients for in vitro organ cultures.…”
Section: Introductionmentioning
confidence: 99%